Street earnings as a mediator of the effect of intellectual capital disclosure, customer value, and research development activities on firm value - Pane, Zulfikar Ikhsan; Sembel, Roy; Agustine, Yvonne (Technium Social Sciences Journal, 2021)
This study is driven by the phenomenon of earnings indicators that can mislead investors due to managers’ personal interests. As a result, investors would seek alternative earnings through analysts serving as intermediaries, referred to as street earnings. Street earnings are considered more predictive, informative, and more likely to be used to assess firm value. Furthermore, non-financial information from the corporation can affect street earnings. As a result, this study attempts to determine whether street earnings affect firm value while also determining whether it can mediate the relationship between non-financial information on firms with firm value. This analysis makes use of 392 observations from manufacturing firms between 2015 and 2020. SPSS 25 and the Sobel test are used to conduct data analysis. One of the three hypothesis is proven, namely that research and development activities directly and indirectly affect street earnings and firm value. If street earnings can moderate the relationship between the two variables, this conclusion is also supported by the Sobel test.